Phenylbutyrate therapy for maple syrup urine disease - Brunetti-Pierri, Nicola; Lanpher, Brendan; Erez, Ayelet; Ananieva, Elitsa A.; Islam, Mohammad; Marini, Juan C.; Sun, Qin; Yu, Chunli; Hegde, Madhuri; Li, Jun; Wynn, R. Max; Chuang, David T.; et al. (Human molecular genetics, 2011)
Therapy with sodium phenylacetate/benzoate or sodium phenylbutyrate in urea cycle disorder patients has been associated with a selective reduction in branched-chain amino acids (BCAA) in spite of adequate dietary protein intake. Based on this clinical observation, we investigated the potential of phenylbutyrate treatment to lower BCAA and their corresponding α-keto acids (BCKA) in patients with classic and variant late-onset forms of maple syrup urine disease (MSUD). We also performed in vitro and in vivo experiments to elucidate the mechanism for this effect. We found that BCAA and BCKA are both significantly reduced following phenylbutyrate therapy in control subjects and in patients with late-onset, intermediate MSUD. In vitro treatment with phenylbutyrate of control fibroblasts and lymphoblasts resulted in an increase in the residual enzyme activity, while treatment of MSUD cells resulted in the variable response which did not simply predict the biochemical response in the patients. In vivo phenylbutyrate increases the proportion of active hepatic enzyme and unphosphorylated form over the inactive phosphorylated form of the E1α subunit of the branched-chain α-keto acid dehydrogenase complex (BCKDC). Using recombinant enzymes, we show that phenylbutyrate prevents phosphorylation of E1α by inhibition of the BCKDC kinase to activate BCKDC overall activity, providing a molecular explanation for the effect of phenylbutyrate in a subset of MSUD patients. Phenylbutyrate treatment may be a valuable treatment for reducing the plasma levels of neurotoxic BCAA and their corresponding BCKA in a subset of MSUD patients and studies of its long-term efficacy are indicated.